Effects of Interrupted Wetness Periods on Conidial Germination, Germ Tube Elongation and Infection Periods of Botryosphaeria dothidea Causing Apple White Rot - Kim, Ki Woo; Kim, Kyu Rang; Park, Eun Woo (The plant pathology journal, 2016)
Responses of Botryosphaeria dothidea to interrupted wetness periods were investigated under in vivo and in vitro conditions. Conidia of B. dothidea were allowed to germinate on apple fruits under wetting condition at 25ºC for 5 hr. They were air-dried for 0, 1, 2 or 4 hr, and then rewetted at 25ºC for 5 hr. Following an initial wetness period of 5 hr, 83% of the conidia germinated. The percent conidial germination increased to 96% when wetting was extended continuously another 5 hr. However, no further conidial germination was observed when wetting was interrupted by dry periods of 1, 2 and 4 hr, resulting in 83, 81 and 82%, respectively. The mean length of the germ tubes was 37 μm after 5 hr of wetting and elongated to 157 μm after 10 hr of continuous wetting. On the other hand, interruption of wetting by a dry period of 1 hr or longer after the 5 hr of initial wetting arrested the germ tube elongation at approximately 42 μm long. Prolonged rewetting up to 40 hr did not restore germ tube elongation on slide glasses under substrate treatments. Model simulation using weather data sets revealed that ending infection periods by a dry period of at least 1 hr decreased the daily infection periods, avoiding the overestimation of infection warning. This information can be incorpo- rated into infection models for scheduling fungicide sprays to control apple white rot with fewer fungicide applications.